Synthesis, Characterization and Antibacterial Activity of Novel 1,3-Diethyl-1,3-bis(4-nitrophenyl)urea and Its Metal(II) Complexes - Hoda Pasdar; Bahare Hedayati Saghavaz; Naser Foroughifar; Mehran Davallo (Molecules, 2017)
A bioactive ligand and its dinuclear metal(II) complexes were synthesized and characterized by Fourier-transform infrared spectroscopy (FT-IR), ultraviolet-visible (UV-Visible), nuclear magnetic resonance (1H-NMR), mass spectroscopy and molar conductance measurements. The ligand has been crystalized in the monoclinic system with a P21/c space group. The biological activities of metal complexes were evaluated using disc diffusion and broth dilution methods. In vitro antibacterial activities of the ligand and their metal complexes were examined against two Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and two Gram-negative bacteria (Escherichia coli and Serratia marcescens) and compared to the standard drugs. It was found that metal complexes displayed much higher antibacterial activities and better inhibitory effects than that of the ligand and standard drugs. Among these complexes, the compound having Zn-metal showed greater antibacterial activity against all four tested bacteria and was more effective against Serratia marcescens with the zone inhibition diameter of 26 mm and MIC value of 31.25 µg/mL.